Uma proposta de bula para software - Lima, Fernando Cesar de (2015)
This research proposes a package insert for software that makes it possible to gather information related to the functional and non-functional requirements of a particular software, following a pre-defined structure. The bibliographic references that supports the work consists of theories relating to transparency, software transparency and mind maps. Discusses the transparency given to the information and processes of public and private initiatives. Provides subsidies for basic conception of mental maps, proposed by Tony Buzan, in order to justify its use in the work. The proposal combines the idea of pharmaceutical inserts, regulated by the National Health Surveillance Agency – ANVISA, to the concepts of mind maps. Complemented by experimental research, this study found the software package insert for efficiency in the transmission of knowledge through an experiment involving 326 participants. It brings up as result a model of package insert for software that may be used by the industry in order to increase one of the transparency’s characteristics: the understandability.